Advancements in asphalt pavement recycling: Integrating falling weight impact signals for enhanced rehabilitation efficiency - Mohan Zhao; Yu Liu; Xinnan Xu; Yuhao Pei; Chengmiao Zhang; Chaofan Wu (Case Studies in Construction Materials)
The fracturing technology has been gradually applied to the field of semi-rigid base, but the current fracturing technology evaluation means cannot achieve comprehensive and real-time evaluation. Therefore, this study introduces a method for the real-time evaluation of fractured semi-rigid pavements. Utilizing falling weight impact acceleration signals, this approach allows for immediate assessment of pavement conditions, addressing the critical challenge of evaluating and enhancing the recycling process of old asphalt bases. Through comprehensive theoretical analysis, indoor non-destructive experiments, and field validations, we demonstrate a significant correlation between impact signals and pavement resilience. This method achieves an identification accuracy of up to 90.90 %, showcasing its potential to significantly improve construction efficiency, reduce resource wastage, and extend pavement life. This technology promises to significantly enhance the quality and efficiency of semi-rigid base asphalt pavement recycling, effectively extending the lifespan of recycled pavements.